Pilgrimage Tourism and its Impact at Naina Devi Shrine (Bilaspur, Himachal Pradesh) - Kumar, Ravi Bhushan; Singh, Gurcharan; Singh, Lakhvinder (Gyan Management Journal, 2015)
Pilgrimage tourism has become the fastest growing segment of tourism industry and every year, millions of people are attracted to visit religious destinations around the world to pay the bow at different shrines. This in turn brings enormous economic and non-economic gains to religious destinations. The present study focus on pilgrimage tourism and its socio-economic and environmental impact at Naina Devi in Bilaspur. The data for this study were collected by adopting qualitative research method such as previous studies has been reviewed for pilgrimage tourism and for measuring the impact the local residents, shopkeepers, tourism professionals such as hoteliers, transport agencies, dhabawaflas, local vendors etc. were discussed. The findings of the study revealed positive impacts of pilgrimage tourism at Naina Devi. However there are a quite number of negative impacts for a number of tourism development measures. So , there is need to concentrate on tourism developments that are fulfilling the requirements of sustainable tourism development in the study area.